Head Down Tilt Bed Rest Plus Elevated CO2 as a Spaceflight Analog: Effects on Cognitive and Sensorimotor Performance - Lee, Jessica K.; De Dios, Yiri; Kofman, Igor; Mulavara, Ajitkumar P.; Bloomberg, Jacob J.; Seidler, Rachael D. (Frontiers in Human Neuroscience, 2019)
Long duration head down tilt bed rest (HDBR) has been widely used as a spaceflight analog environment to understand the effects of microgravity on human physiology and performance. Reports have indicated that crewmembers onboard the International Space Station (ISS) experience symptoms of elevated CO2 such as headaches at lower levels of CO2 than levels at which symptoms begin to appear on Earth. This suggests there may be combinatorial effects of elevated CO2 and the other physiological effects of microgravity including headward fluid shifts and body unloading. The purpose of the current study was to investigate these effects by evaluating the impact of 30 days of 6° HDBR and 0.5% CO2 (HDBR+CO2) on mission relevant cognitive and sensorimotor performance. We found a facilitation of processing speed and a decrement in functional mobility for subjects undergoing HDBR+CO2 relative to our previous study of HDBR in ambient air. In addition, nearly half of the participants in this study developed signs of Spaceflight Associated Neuro-ocular Syndrome (SANS), a constellation of ocular structural and functional changes seen in approximately one third of long duration astronauts. This allowed us the unique opportunity to compare the two subgroups. We found that participants who exhibited signs of SANS became more visually dependent and shifted their speed-accuracy tradeoff, such that they were slower but more accurate than those that did not incur ocular changes. These small subgroup findings suggest that SANS may have an impact on mission relevant performance inflight via sensory reweighting.